Selenium Toxicity Induced Physiological and Biochemical Alterations in Maize Seedlings - Mustafa Yıldız; Emre Pehlivan; Hakan Terzi (European Journal of Biology)
Objective: Selenium (Se) is not necessary for plants but alleviates the harmful effects of abiotic stresses. Indeed, high Se levels cause toxicity by inducing oxidative stress and disrupting several metabolic processes. However, the underlying mechanisms remain poorly understood.Materials and Methods: The effects of Se toxicity on the morphological and physiological attributes of hydroponically grown maize (Zea mays L.) seedlings were illustrated. Five-day-old seedlings were subjected to 0 (control), 50, and 100 μMSe. After ten days, the treated seedlings were harvested to analyze growth, cell viability, photosynthetic pigments, lipid peroxidation, reactive oxygen species (ROS) accumulation, and enzymatic antioxidants.Results: The results indicated that excess Se resulted in phytotoxicity, as demonstrated by reduced seedling growth, root activity, and chlorophyll accumulation but higher malondialdehyde content. Se also increased oxidative stress, as illustrated by the accumulation of ROS, lipid peroxidation, and loss of membrane integrity. The antioxidative system was induced to detoxify ROS through the superoxide dismutase, guaiacol peroxidase, and catalase enzymes. Excess Se increased catalase activity, while the opposite happened in superoxide dismutase and guaiacol peroxidase activities.Conclusion: These results may improve the understanding of Se phytotoxicity in plants.